Purification of a Fc-Fusion Protein with [Bathophenathroline:metal] Complexes - Thisara Jayawickrama Withanage; Ron Alcalay; Olga Krichevsky; Ellen Wachtel; Ohad Mazor; Guy Patchornik (Antibodies)
In this study, we assess an alternative Fc-fusion protein purification method that does not rely on chromatographic media or ligands. Recombinant human acetylcholinesterase, fused to the Fc domain of human IgG1 (henceforth, AChE-Fc), was purified with precipitated aromatic complexes composed of the bathophenanthroline (henceforth, batho) chelator with either Zn2+ or Cu2+ ions (i.e., [(batho)3:Zn2+] or [(batho)2:Cu2+]) in the presence of polyethylene glycol 6000 (PEG-6000). In a three-step purification process conducted at pH 7, AChE-Fc was captured by the aromatic complexes (Step 1); unbound or weakly bound protein impurities were removed with 20 mM NaCl (Step 2); and AChE-Fc was then extracted at pH 7 (Step 3) using 100 mM Na citrate buffer in 250 mM NaCl. Purified AChE-Fc was not aggregated (as determined by dynamic light scattering (DLS) and Native PAGE). However, full enzymatic activity was only preserved with the [(batho)3:Zn2+] complex. Interaction between AChE-Fc and [(batho)3:Zn2+] led to ~83–88% overall protein yield. Thirty-fold process upscaling by volume required only proportional increase in the amounts of [(batho)3:Zn2+] and PEG-6000. Efficient (95–97%) chelator recycling was achieved by recrystallization. Chelator leaching into purified AchE-Fc was estimated to be ~0.3% relative to the total amount used. Taken together, this novel procedure has the potential to provide an economical and practical avenue for the industrial purification of Fc-fusion proteins.